Aporte de la gerencia del talento humano en los procesos de gestión de calidad (2020)
This research entitled contribution of human talent management in quality management processes seeks to generate awareness strategies that boost efficiency, creativity and innovation and thereby attract competitiveness, in the development of the project will describe the awareness actions that develops the management of human talent to the quality management system, for this it seeks to generate programs, campaigns, conferences, forums that allow the sensitization of staff by converting us into learning centers that generate, maintain and translate it into actions of added value since the permanence of an organization currently depends on the investment made in intangibles, such as innovation and development of human capital since the greater the magnitude of learning, the greater the preparation to face the changes and fluctuations of the organizational environment to achieve stay in the competitive market.